(untitled) (Journal of the College of Basic Education, 2022)
In light of the growth of eco-tourism, which has become an important element in the tourism industry and development economic and social development at the international and local levels, as it represents an important and basic economic resource countries, especially those characterized by limited resources. Therefore, this study acquires special importance. Because Researching the rehabilitation of one of the successful means in the field of managing natural reserves using a system